VATS surgery for anatomical lung resection: a different approach for every surgeon - Migliore, Marcello (Video-Assisted Thoracic Surgery; Vol 1 (November 2016): Video-Assisted Thoracic Surgery, 2016)
Video assisted thoracic surgery (VATS) is becoming the standard of practice in the surgical treatment of lung cancer (1). French et al. made an important contribution having reported an interesting experience of transition from multiple ports to single port VATS for anatomic pulmonary resection (2), and they conclude that patient safety and oncologic quality are preserved during the transition period.